Relationship between domain-specific physical activity and cognitive function in older adults - findings from NHANES 2011-2014 - Sijun Wu; Lin Wang; Shijie Liu; Juancai Qi; Fengrui Shi; Huiqi Zhuang; Youling Qian; Linqi Mei; Maolin Zhang (Frontiers Media S.A., 2024)
ObjectiveTo determine the relationship between domain-specific physical activity (PA) (e.g., occupational PA [OPA], transport-related PA [TPA], and recreational PA [RPA]) and cognitive function in older adults.MethodsThe data was obtained from the 2011-2014 cycle of the NHANES. We utilized weighted multivariate linear regression models among the included 2,924 people aged 60 years or older for our purposes.ResultsRPA and total PA according to WHO guidelines were associated with verbal fluency (RPA β: 1.400, 95% CI: 0.776, 2.024, p = 0.002; total PA β: 1.115, 95% CI: 0.571, 1.659, p = 0.001), processing speed and executive function (RPA β: 2.912, 95% CI. 1.291, 4.534, p = 0.005; total PA β: 2.974, 95% CI: 1.683, 4.265, p < 0.001) were positively correlated, and total PA was correlated with delayed memory performance (β: 0.254, 95% CI: 0.058, 0.449, p = 0.019). No significant association was observed between OPA, TPA, and various aspects of cognitive function among individuals over 60 years.ConclusionThere was no noteworthy correlation discovered between OPA and TPA in relation to cognitive function. However, RPA and total PA exhibited significant associations with verbal fluency, processing speed, and executive function. Additionally, maintaining PA levels ranging from 600 to 1,200 MET-min/week would yield the most favorable outcomes for cognitive function.